2011
DOI: 10.1534/genetics.111.132332
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Salicylic Acid-Mediated Defense Signaling Networks in Arabidopsis

Abstract: Properly coordinated defense signaling networks are critical for the fitness of plants. One hub of the defense networks is centered on salicylic acid (SA), which plays a key role in activating disease resistance in plants. However, while a number of genes are known to affect SA-mediated defense, relatively little is known about how these gene interact genetically with each other. Here we exploited the unique defense-sensitized Arabidopsis mutant accelerated cell death (acd) 6-1 to dissect functional relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 58 publications
(103 reference statements)
4
79
0
Order By: Relevance
“…It has been shown that PAD4 and EDS1 participate not only in resistance to pathogens but also in the transduction of photooxidative stress signals resulting in cell death and growth inhibition. Cell death and growth inhibition phenotypes of lsd1, acd6-1, cpr1, and cpr6 mutants require the presence of PAD4 and EDS1, as demonstrated by the rescue of mutant phenotypes in double mutants with pad4 or eds1 (Jirage et al, 2001;Rust茅rucci et al, 2001;Mateo et al, 2004;Ochsenbein et al, 2006;M眉hlenbock et al, 2008;Ng et al, 2011). The SA amplification loop is also crucial for cell death and senescence, increased SA content, and gene expression changes in saul1 mutants challenged by low light (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…It has been shown that PAD4 and EDS1 participate not only in resistance to pathogens but also in the transduction of photooxidative stress signals resulting in cell death and growth inhibition. Cell death and growth inhibition phenotypes of lsd1, acd6-1, cpr1, and cpr6 mutants require the presence of PAD4 and EDS1, as demonstrated by the rescue of mutant phenotypes in double mutants with pad4 or eds1 (Jirage et al, 2001;Rust茅rucci et al, 2001;Mateo et al, 2004;Ochsenbein et al, 2006;M眉hlenbock et al, 2008;Ng et al, 2011). The SA amplification loop is also crucial for cell death and senescence, increased SA content, and gene expression changes in saul1 mutants challenged by low light (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, the change of acd6-1 dwarfism induced by second-site mutations could be conveniently used as a visual readout to provide a rapid assessment of the effect of these second-site mutations in some genes on defense responses. acd6-1 has been successfully used in genetic analyses to reveal epistatic relationships between defense mutants and in a genetic screen to identify, to our knowledge, novel defense genes (Song et al, 2004;Lu et al, 2009;Ng et al, 2011;Wang et al, 2011aWang et al, , 2011bWang et al, , 2014a. We found that while acd6-1 sim-1 resembled acd6-1 in plant morphology, acd6-1 smr1-1 and acd6-1 sim-1 smr1-1 were significantly larger than acd6-1 plants (Fig.…”
Section: Smr1 Contributes To Sa-mediated Defensementioning
confidence: 76%
“…These results prompted us to ask whether SA could affect cell-cycle progression as part of downstream signaling of some cell-cycle genes. To test this, we analyzed cell ploidy in the major SA biosynthetic mutant sid2-1 (Wildermuth et al, 2001;Ng et al, 2011) and the SA signaling mutant npr1-1 (Dong, 2004;Lu, 2009;Fu and Dong, 2013). Our results show that both sid2-1 and npr1-1 had significantly increased numbers of 4C cells but reduced numbers of 8C and 16C cells (Fig.…”
Section: Sa Signaling Affects Cell-cycle Progressionmentioning
confidence: 92%
See 1 more Smart Citation
“…EDS1 and PAD4 are interacting proteins that regulate pathogen signaling from TIR-NB-LRR receptors (Rust茅 rucci et al, 2001;Heidrich et al, 2011;Rietz et al, 2011). Furthermore, EDS1 and/or PAD4 regulates cell death in a variety of contexts, including light signaling (M眉 hlenbock et al, 2008), treatments with the chloroplastic-ROS-generating compound methyl viologen (Straus et al, 2010), and suppression of cell death in lesion mimic mutants (Rust茅 rucci et al, 2001;Ng et al, 2011;. The molecular mechanisms The indicated genotypes were exposed to O 3 for 6 h (350 nl l 脌1 related to the regulation of cell death via EDS1 are still unknown.…”
Section: Regulation Of Cell Death By Apoplastic Rosmentioning
confidence: 99%